All-in-one biofabrication and loading of recombinant vaults in human cells. (1st April 2022) - Martín, Fernando; Carreño, Aida; Mendoza, Rosa; Caruana, Pablo; Rodriguez, Francisco; Bravo, Marlon; Benito, Antoni; Ferrer-Miralles, Neus; Céspedes, M Virtudes; Corchero, José Luis
Abstract: One of the most promising approaches in the drug delivery field is the use of naturally occurring self-assembling protein nanoparticles, such as virus-like particles, bacterial microcompartments or vault ribonucleoprotein particles as drug delivery systems (DDSs). Among them, eukaryotic vaults show a promising future due to their structural features, in vitro stability and non-immunogenicity. Recombinant vaults are routinely produced in insect cells and purified through several ultracentrifugations, both tedious and time-consuming processes. As an alternative, this work proposes a new approach and protocols for the production of recombinant vaults in human cells by transient gene expression of a His-tagged version of the major vault protein (MVP-H6), the development of new affinity-based purification processes for such recombinant vaults, and the all-in-one biofabrication and encapsulation of a cargo recombinant protein within such vaults by their co-expression in human cells. Protocols proposed here allow the easy and straightforward biofabrication and purification of engineered vaults loaded with virtually any INT-tagged cargo protein, in very short times, paving the way to faster and easier engineering and production of better and more efficient DDS.